Handwashing among schoolchildren in an ethnically diverse population in northern rural Vietnam - Le Thi Thanh Xuan; Luu Ngoc Hoat (Taylor & Francis Group, 2013)
Background: Handwashing with soap (HWWS) is a simple and effective measure to prevent transmission of fecal–oral disease and other infectious diseases in school-age children. To promote the behavior, we need to understand their HWWS compliance. The aim of this article is to describe handwashing behavior and HWWS compliance and to identify associated factors among schoolchildren in the multiethnic rural area of northern Vietnam. Methods: The study was conducted in six primary and secondary schools and in the homes of four ethnic villages in northern Vietnam. Quantitative methods included face-to-face interviews with, and demonstration of handwashing protocol to, 319 schoolchildren in first, fourth, and seventh grades. Qualitative methods included structured observations at six schools and 20 homes comprising 24 children. The dependent variable was the self-reported HWWS behavior (yes/no). The independent variables included grade, school type, gender, ethnicity group, owning home latrine, and household assets. Logistic regression modelling was performed to examine associations between HWWS behavior and demographic factors. Results: Among the 319 schoolchildren interviewed, 66% reported HWWS. Through the demonstration protocol, only 10 out of 319 schoolchildren, performed HWWS satisfactorily. The percentage of students who washed their hands at recommended times (30–60 sec) was 58%. This proportion increased by grade (from 34% among grade 1 to 67% among grade 7; p<0.05). Correlates of self-reported HWWS were more common in higher grades [grade 4 vs. grade 1: odds ratio (OR)=4.14 (2.00–8.56), grade 7 vs. grade 1: OR=7.76 (3.67–16.4)] and less common in ethnic minority groups [Xa Phó vs. Kinh-Tay: OR=0.28 (0.11–0.70)]. All 20 homes of schoolchildren visited had soap and water but none of the six schools had soap for handwashing. Conclusions: This article describes poor compliance of schoolchildren with HWWS in a multiethnic population in Vietnam. Education on handwashing needs to be prioritized among multiethnic children at school.